IMPLEMENTASI PERATURAN DAERAH KABUPATEN OGAN KOMERING ULU NOMOR 15 TAHUN 2013 TENTANG PEMBINAAN, PENGAWASAN DAN PENGENDALIAN KETERTIBAN UMUM (STUDI PADA TUGAS PEMBINAAN DAN PENGAWASAN TEMPAT HIBURAN MALAM) - Rio Satria Wibowo; Marratu Fahri; Rahmat Saleh; Yahnu Wiguno Sanyoto (Jurnal Riset Multidisiplin Edukasi, 2026)
This research seeks to examine the implementation of Ogan Komering Ulu Regency Regional Regulation Number 15 of 2013 regarding the guidance and supervision of public order control. A qualitative research design was applied, utilizing in-depth interviews with key informants comprising members of the Civil Service Police Unit, officials from the Licensing Office, and managers of night entertainment establishments. The data obtained were analyzed descriptively to explore the implementation mechanisms, existing constraints, and the overall effectiveness of the regulation. The findings reveal that the enforcement of Regional Regulation Number 15 of 2013 has been conducted through regular monitoring activities, field inspections, and coordination among relevant government agencies. Nevertheless, the implementation process encounters several obstacles, including inadequate human resources and supporting facilities, as well as opposition from certain segments of the community and business actors. Despite these challenges, supervisory personnel exhibited a high level of professionalism and dedication in maintaining public order. However, further enhancement of coordination and monitoring systems is required to improve regulatory effectiveness. Based on these findings, the study suggests strengthening personnel capacity, improving inter-agency collaboration, and intensifying public outreach and awareness programs targeting both the community and business operators. Through these measures, the regulation can be implemented more effectively, thereby contributing to improved public order conditions in Ogan Komering Ulu Regency.